Effect of Diaphragmatic Respiratory Training on Some Pulmonary Indexes in Older People With Chronic Obstructive Pulmonary Disease - Mojtaba Amini; Mandana Gholami; Hosein Aabed Natanzi; Nader Shakeri; Hamidreza Haddad (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Chronic Obstructive Pulmonary Disease (COPD) is one of the most important progressive pulmonary disorders. Diaphragmatic dysfunction is an essential factor in the worsening and progression of symptoms in patients with COPD. Therefore, we investigated the effect of diaphragmatic respiratory training on some pulmonary indexes in these patients. Methods & Materials This quasi-experimental study type with pretest-posttest design, 16 male patients (Mean±SD=55 ± 5.4 y) with moderate COPD were selected through convenient sampling method and were randomly divided into two groups of 8 (diaphragmatic training and control group). A demographic questionnaire was used to control the inclusion criteria. Maximal inspiratory pressure, forced expiratory volume in 1 second, and respiratory rate per minute were measured by laboratory equipment. The training group performed the respiratory exercises 3 sessions per week for 8 weeks. The control group did not do any exercise. After the end of training, the pulmonary indexes were re-evaluated. Statistical data were analyzed by ANOVA and Tukey's post hoc test in SPSS21. Results The results indicated that diaphragmatic respiratory exercises had a significant effect on pulmonary indexes (P=0.001). There was no improvement in any of the variables in the control group (P ˃ 0.05). Conclusion Diaphragmatic respiratory training seems to play an essential role in improving the respiratory indexes of patients with pulmonary disease. The results of our study showed that respiratory training improves the respiratory function of patients and should be included in the pulmonary rehabilitation program for these patients.